Rancang Bangun Mesin Pengiris Singkong - Husman Husman; Sugeng Ariyono (Manutech : Jurnal Teknologi Manufaktur, 2018)
The Bangka Belitung Islands have enormous natural resources, including mining products, forest products, marine products and plantation products. The cultivated plantation can consist of groups or individuals. One of the plantation products managed by the community in Belitung, especially in the Regency of Bangka, is cassava. Various kinds of food are processed using raw cassava, one of which is produced by a home industry in other words Small and Medium Industries (IKM) in the village of Banyu Asin, Bangka Regency. Using a simple production tool made of wood and fitted with a cutting knife to slice cassava and use a tool that was bought from the market made of plastic base material and installed a blade to slice manually. This research was conducted to help make a machine that can simplify and reduce the energy of workers in the process of making cassava chips. The method used to solve this problem is starting with the compilation of a list of required product requirements, making and selecting concepts, designing components, making detailed technical drawings, making and assembling and testing the function of the tools. Testing the function of the tool is done in order to find out whether the tool that has been made can function properly and can do the desired slicing. The results of the trial process of the cassava slicing machine made were able to increase productivity and slice cassava as much as 96 kg per hour with one operator. Previously, to slice 90 kg of cassava takes 3 hours with 2 operators.